(untitled) (Revista Espinhaço, 2025)
The objective of the study was to test the Meyer model in the management of four plant communities located in the district of Magude in the province of Maputo. In the study were established in total 163 rectangular plots of 100X20m, in each plot was measured the DBH 10cm of all trees. Were sampled 4243 woody individuals in all stands, which are distributed in 16 botanical families, 75 species and 32 genres. The botanical family with the highest number of species in the area was Fabaceae. The species Acacia nigrescens was the most prominent because it had the highest number of individuals in all communities. The dendrometric variables used in the model adjustment report a larger diameter of 50, 65, 60, 43cm in Duco, Motaze-Sede, Ungumbane and Waficula. The forest of Duco had a density of 88.9arvha-1 and a maximum basal area of 34.2603m2, 119.14arvha-1 and basal area of 10.9654m2 for Motaze-Sede, 86.88arvha-1 and basal area of 31.76247m2 for Ungumbane and the community of Waficula had a density of 148.93arvha-1 and a basal area of 12.7844m2. From the Meyer model it was observed the permanence of 55% of remaining basal area for the community of Waficula, 60% for the community of Duco, 58% for the community of Ungumbane 1 and 57% of remaining basal area for the community of Motaze the proportion of the basal area remaining the balanced communities and the Meyer model proved to be efficient to make the forests sustainable allowing exploration of the largest diameter classes.